2014
DOI: 10.1152/ajpcell.00164.2014
|View full text |Cite
|
Sign up to set email alerts
|

The mitosis-regulating and protein-protein interaction activities of Astrin are controlled by Aurora-A-induced phosphorylation

Abstract: CT. The mitosis-regulating and protein-protein interaction activities of Astrin are controlled by Aurora-A-induced phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…6b ), in agreement with a recent report 38 . Another interesting partner of CDC20B identified in a second unbiased interactome study 40 was SPAG5 (Astrin), which was reported to control timely activation of Separase during the cell cycle 41 , 42 . Using the same strategy as above, we could detect CDC20B and SPAG5 in the same complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6b ), in agreement with a recent report 38 . Another interesting partner of CDC20B identified in a second unbiased interactome study 40 was SPAG5 (Astrin), which was reported to control timely activation of Separase during the cell cycle 41 , 42 . Using the same strategy as above, we could detect CDC20B and SPAG5 in the same complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to what is known about Aurora B, it should be noted that Astrin also interacts with Aurora kinase A (AURKA), which is another member of the mitotic-regulated serine/threonine kinase family ( Bischoff and Plowman, 1999 ; Du et al, 2008 ; Chiu et al, 2014 ). Interestingly, the relationship between Astrin and Aurora A appears to have two distinct characteristics.…”
Section: The Dynamic Localization Of Astrin In Mitosismentioning
confidence: 99%
“…Second, Astrin is the phosphorylated substrate of Aurora A, and Aurora-A is essential for Astrin to regulate the activity of separase. Further, the Aurora A phosphorylation site of Astrin is important for the association of Astrin with additional interacting proteins including CLASP1, LC8, SKAP, and others ( Chiu et al, 2014 ). In short, the relationship between Astrin and Aurora A warrants further study.…”
Section: The Dynamic Localization Of Astrin In Mitosismentioning
confidence: 99%
“…Astrin is known to be phosphorylated at multiple sites (33,34), it is unclear whether Astrin phosphorylation by mitotic kinases regulates its KT targeting. This uncertainty prompted us to research other phosphorylation sites, the mitotic kinase(s) responsible for Astrin targeting to KTs, and the resulting KT structural ensemble.…”
Section: Astrin Is Phosphorylated In the N-terminal Region During Mitmentioning
confidence: 99%
“…Glycogen synthase kinase 3␤ (Gsk3␤) phosphorylates Astrin at Thr-111, Thr-937, Ser-974, and Thr-978 to regulate its spindle-forming ability but has no effect on localization (33). Aurora A regulates separase activity and the interaction of Astrin with Kinastrin/Skap and Clasp1␣ by phosphorylating Astrin at Ser-115 to promote mitotic progression (34).…”
mentioning
confidence: 99%